An economic loss model for failure of sewer pipelines. Issue 10 (3rd October 2018) - Elmasry, Mohamed; Hawari, Alaa; Zayed, Tarek
Abstract: Estimating the costs of failure for sewer pipelines is usually accompanied with uncertainties because of the difficulty in capturing the relationship between the physical and economical characteristics of failed pipelines. To reduce such uncertainties economic loss models are usually used to evaluate the consequences of failure. This paper presents a methodology to estimate economic loss as a result of sewer pipelines' failure using cost benefit analysis approach. Costs of sewer pipelines' failure in addition to costs resulting from avoiding such failures are identified and analysed. To validate the proposed methodology, actual costs from a real failure incident were compared with the proposed model outputs. The model could estimate the direct and indirect costs with a deviation ranging between 10–12% and 22–30%, respectively. By implementing the proposed methodology on two case studies, it was found that the indirect costs as a result of sewer pipelines' failure represent a significant portion ranging between 89 and 94% of the total costs of failure. Also, it was found that costs related to environment, delays to work and traffic disruptions contribute by 12–35% to the indirect costs.